Surface sputtering with nanoclusters: the relevant parameters. (1st March 2012) - Delcorte, A.; Restrepo, O. A.; Czerwinski, B.; Garrison, B. J.
<x xml:space="preserve">Abstract</x> In this contribution, we compare the results of our recent molecular dynamics simulations with data already published by us and by other authors to identify the relevant physical parameters governing observables such as the range, the damaged volume, the crater shape, the sputtering yield, the emission of molecules and fragments, and the chemical reactions induced in organic solids by cluster projectiles. Among the considered physical quantities, we show for instance that the total cluster energy, the energy per atom/per nucleon in the cluster and, importantly, the mass matching between the cluster and target constituents have a major effect on the physics of the interaction. The evolution of the observables as a function of these basic physical parameters is illustrated and discussed as well as certain implications for organic surface characterization using cluster ion beams. Copyright © 2012 John Wiley & Sons, Ltd.